Exploring consumer preferences towards electric vehicles: The influence of consumer innovativeness. (March 2016) - Morton, Craig; Anable, Jillian; Nelson, John D.
Abstract: The diffusion of electric vehicles (EVs) is regarded as an important aspect of government policy which aims to generate a transition to a low-carbon mobility system in the United Kingdom and the wider European context. This paper investigates consumer demand for EVs by examining the influence of consumer innovativeness alongside attitudes concerning the functional capabilities of EVs over EV preferences. A conceptual framework is developed and applied which includes measurements of innovativeness at both an adoptive level, through an assessment of technology ownership, and at an innate level, by measuring a cohort of psychological and sociological factors. Additionally, the framework incorporates measurements of attitudes towards the functional performance of EVs to determine their effect on preferences. Data has been collected through the application of a self-completion household survey distributed over the cities of Dundee and Newcastle upon Tyne in the United Kingdom. Results of the analysis indicate that adoptive innovativeness and attitudes concerning the functional performance of EVs significantly affect preferences for plug-in hybrid electric vehicles (PHEVs) and battery electric vehicles (BEVs).